TET2 mutations, myelodysplastic features, and a distinct immunoprofile characterize blastic plasmacytoid dendritic cell neoplasm in the bone marrow. Issue 12 (30th September 2013) - Alayed, Khaled; Patel, Keyur P.; Konoplev, Sergej; Singh, Rajesh R.; Routbort, Mark J.; Reddy, Neelima; Pemmaraju, Naveen; Zhang, Liping; Shaikh, Abdulaziz Al; Aladily, Tariq N.; Jain, Nitin; Luthra, Rajyalakshmi; et al.
<x xml:space="preserve">Abstract</x> Distinguishing blastic plasmacytoid dendritic cell neoplasm (BPDCN) from acute myeloid leukemia (AML) is gaining increased importance because of emerging differences in therapeutic approaches, and this distinction can be problematic in bone marrow specimens. We identified retrospectively 16 patients with bone marrow involvement by BPDCN: 11 men and 5 women with a median age of 62.5 years (range, 19–86 years). Myelodysplastic changes were observed in five patients. Immunophenotypic analysis showed that the neoplastic cells were positive for CD4, CD123, TCL‐1, and HLA‐DR and were negative for CD3, CD8, CD13, CD19, CD34, and myeloperoxidase. Other antigens expressed by subsets of BPDCN cases included the following: CD56 (13/15; 81%), CD33 (7/10; 70%), CD7 (11/14; 69%), TdT (5/15; 33%), CD2 (5/11; 31%), CD117 (2/9; 22%), and CD5 (2/13; 15%). Conventional cytogenetic analysis showed chromosomal abnormalities in 6 of 13 (46%) cases analyzed, of which 3 cases had −13/13q−. Targeted next‐generation sequencing performed on five BPDCN cases identified TET2 (ten eleven translocation 2) mutations and no other AML‐associated mutations. In conclusion, BPDCN in the bone marrow has a characteristic immunoprofile (CD4+, CD56+, CD123+, and TCL‐1+) and appears to be commonly associated with myelodysplastic features and a high frequency of TET2 mutations in the absence of other mutations commonly observed in AML. Am. J. Hematol. 88:1055–1061, 2013. © 2013 Wiley Periodicals, Inc.